The anti-corruption handbook : how to protect your business in the global marketplace - Olsen, William P. (John Wiley & Sons, 2010)
* Fighting Global Corruption skilfully explores the risk of doing business in the global marketplace and the precautions companies and organizations can take to deter corruption